Inventor Matrosov I.K. and brake gear development - S. S. Dovhaniuk (History of science and technology, 2014)
In the paper the analysis of technical solutions about the design changes in the air diffusers of Matrosov system cargo type to improve the performance of automatic brakes of heavyweight and long formation trains is shown. Comparative characteristics and parameters of air diffusers of Matrosov system, Matrosov I.K. contribution to brake gear improvement are shown.